Cross-cultural determinants of development linguistic personality - Boltayev Chutkul Boltayevich (Academia One, 2023)
The article is devoted to the problem of identification of a language personality’s traits under conditions of cross-cultural communication. It is shown that effective cross-cultural communication is revised under globalization and increasingly intensive social interactions. The results of the authors’ research prove that it is possible to develop a new perspective on the heuristic possibilities of the concept of language personality to ensure the effectiveness of cross-cultural communications. This applies above all to the understanding of culture, cultural codes, verbal, nonverbal communication and preverbal, development of value measurement and understanding, and behavior adoption patterns. We propose to identify a language personality as a nationally specific communicant type that has a culturally caused worldview and value system and is capable of crosscultural transformation. We identified transitions from a “mono” language personality to a “multi” language personality. We offer communicative training as a way of resolving cultural gaps in communication. We insist that only a new type of a language personality can effectively integrate and communicate while taking into account cultural peculiarities. Language personality currently acquires multicultural traits resulting from two main types of mobility: virtual and physical. Empirical research shows that two types of mobility are widespread, with typical high demands for the study of an international communication language (English) and local culture.
Keywords: language personality; cross-cultural communication; cross-cultural competence; communicative training